URGENSI AUTOPSI FORENSIK DAN IMPLIKASINYA DALAM TINDAK PIDANA PEMBUNUHAN - Samsudi, Samsudi; Ohoiwutun, Y.A. Triana; Ayudyana Suyudi, Godeliva; Widowati, Widowati (Faculty of Law, Parahyangan Catholic University, 2021)
The court does not always demand or require visum et repertum when examining homicide cases. Forensic autopsy may not be required at all by the criminal court when deciding that the accused is guilty of homicide as charged. The verdict may be reached based on other evidence. The author, using a juridical normative approach, concludes that the absence or presence of a visum et repertum does influence the judge’ consideration and matters to the final verdict. Considering that, regardless of the surviving family’s consent, in cases of unnatural death, forensic autopsy and the making of a visum et repertum should be mandatory.